Using human behaviour change interventions to improve the welfare of working equids in Colombia - Burridge, Jessica (2025)
There are an estimated 116 million working equids that contribute to the daily lives of over 600 million people worldwide. These animals are used for a huge variety of income-generating and non-income generating activities including tourism, agricultural support, mining and transportation. Many of the families these equids support live below the international poverty line. The livelihoods of these individuals as well as the welfare of their equids is often compromised. Health conditions such as equine colic are common within working equid populations, and the consequences of poor welfare can be extremely severe within these populations. There are a number of national and international non-governmental organisations that aim to support the lives of working equids and their owners through a number of methods including provision of free veterinary treatment, advocacy, skills training and community participatory exercises. The lives of working equids are intricately linked with their owners and the wider communities. In order to appropriately support working equids, it is vital to develop a deeper understanding of the communities in which they live and the factors that contribute to their welfare.